Decomposing oceanic temperature and salinity change using ocean carbon change - C. E. Turner; P. J. Brown; K. I. C. Oliver; E. L. McDonagh (Ocean Science, 2022)
As the planet warms due to the accumulation of anthropogenic CO 2 in the atmosphere, the interaction of surface ocean carbonate chemistry and the radiative forcing of atmospheric CO 2 leads to the global ocean sequestering heat and carbon in a ratio that is nearly constant in time. This ratio has been approximated as globally uniform, enabling the intimately linked patterns of ocean heat and carbon uptake to be derived. Patterns of ocean salinity also change as the Earth system warms due to hydrological cycle intensification and perturbations to air–sea freshwater fluxes. Local temperature and salinity change in the ocean may result from perturbed air–sea fluxes of heat and fresh water (excess temperature, salinity) or from reorganisation of the preindustrial temperature and salinity fields (redistributed temperature, salinity), which are largely due to circulation changes. Here, we present a novel method in which the redistribution of preindustrial carbon is diagnosed and the redistribution of temperature and salinity is estimated using only local spatial information. We demonstrate this technique in the NEMO ocean general circulation model (OGCM) coupled to the MEDUSA-2 biogeochemistry model under an RCP8.5 scenario over 1860–2099. The excess changes (difference between total and redistributed property changes) are thus calculated. We demonstrate that a global ratio between excess heat and temperature is largely appropriate regionally with key regional differences consistent with reduced efficiency in the transport of carbon through the mixed layer base at high latitudes. On centennial timescales, excess heat increases everywhere, with the North Atlantic being a key site of excess heat uptake over the 21st century, accounting for 25 % of the total. Excess salinity meanwhile increases in the Atlantic but is generally negative in other basins, consistent with increasing atmospheric transport of fresh water out of the Atlantic. In the North Atlantic, changes in the inventory of excess salinity are detectable in ...